Intracellular Porphyromonas gingivalis Promotes the Proliferation of Colorectal Cancer Cells via the MAPK/ERK Signaling Pathway - Mu, Wenxin; Jia, Yiqun; Chen, Xiaobing; Li, Haoyu; Wang, Zhi; Cheng, Bin (Frontiers in Cellular and Infection Microbiology, 2020)
Porphyromonas gingivalis (P. gingivalis) is a keystone pathogen in periodontitis. However, several clinical studies have revealed an enrichment of P. gingivalis in the stool samples and colorectal mucosa of colorectal cancer patients. Thus, the goal of this study was to determine whether P. gingivalis can promote colorectal cancer progression in vitro. We established an acute infection model (24 h, multiplicity of infection =100) of P. gingivalis invasion of colorectal cancer cells to study the alterations induced by P. gingivalis in the proliferation and cell cycle of colorectal cancer cells. We observed that P. gingivalis can adhere and invade host cells a few hours after infection. Once invaded, P. gingivalis significantly promoted colorectal cancer cell proliferation, and the percentage of S phase cells was increased in the cell cycle assay. However, KDP136, a gingipain-deficient mutant of P. gingivalis 33277, showed a decreased ability to promote colorectal cancer cell proliferation, indicating that gingipain is associated with colorectal cancer cell proliferation. Furthermore, we extracted RNA from colorectal cancer cells for high-throughput sequencing analysis and reconfirmed the results by quantitative polymerase chain reaction and western blot analyses. The results suggested that the MAPK/ERK signaling pathway is significantly activated by P. gingivalis, while these changes were not observed for KDP136. In conclusion, P. gingivalis can invade cells and promote the proliferation of colorectal cancer cells by activating the MAPK/ERK signaling pathway. Gingipain is an essential virulence factor in this interaction.